Clinical and Psychological Aspects of Piercing: A Cross-Sectional Study with Special Attention to Body Dysmorphic Disorder Symptoms, Appearance Anxiety, Body Image Perception and Self-Esteem - Justyna Putek; Jacek C. Szepietowski (Cosmetics)
The aim of this study was to measure the level of self-esteem among individuals with piercings, evaluate body image perception, and screen the study group for body dysmorphic disorder symptoms. Two hundred and six individuals from Poland completed the Appearance Anxiety Inventory (AAI), Body Dysmorphic Disorder Questionnaire-Dermatology Version (BDDQ-DV), Functionality Appreciation Scale (FAS), and Rosenberg Self Esteem Scale (RSES). Differences between groups were determined using a two-sample t-test, post-hoc chi-square test with Bonferroni’s adjustment, the Kruskal–Wallis test, and the Mann–Whitney test. One hundred ninety-six (95.1%) respondents were females, and 10 (4.9%) were males, aged from 15 to 48 years (mean age ± SD = 23.1 ± 6.4 years). Of the respondents, 25.7% screened positive for BDD symptoms according to the AAI and 29.1% screened positive according to the BDDQ-DV. According to the FAS, significantly lower body image was presented by individuals with psychiatric treatment (3.8 ± 0.9 vs. 4.1 ± 0.7, p < 0.05) and by respondents who screened positive for BDD symptoms. Significantly lower self-esteem was reported in individuals with psychiatric comorbidities, psychiatric treatment, and in the BDD-groups according to the RSES (AAI: 24.0 ± 5.6 vs. 30.9 ± 6.0; p < 0.001; BDDQ-DV: 24.0 ± 5.8 vs. 31.3 ± 3.7; p < 0.001). In conclusion, individuals with piercings should be regarded as a group with an increased risk for BDD symptoms.